The most magnificent thing - Spires, Ashley, 1978- (Kids Can Press, 2014)
A little girl has a wonderful idea. With the help of her canine assistant, she is going to make the most magnificent thing! She knows just how it will look. She knows just how it will work. But making the most magnificent thing turns out to be harder than she thinks.